ĐIỀU KIỆN BIẾN CHẤT ĐÁ HOA CHỨA RUBY MỎ QUỲ CHÂU NGHỆ AN - Thắng, Tạ Trọng; Tích, Vũ Văn; Vượng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2016)
Metamorphic petrology of ruby bearing marbles in Quy Chau mineRuby bearing marbles from Quy Chau mine in Bu Khang core complex were studied in detail based on mineral composition and paragenesis analyses. The mineral composition analyse shows that all of these mineral phase are affiniated to aluminum-rich carbonates. The paragenesis analyse explain that this rock was metamorphosed in amphibolite and lower part of granulite faces, corresponding to 774°C and 4 kbars obtained from calcite-dolomite couple.The results obtained  permit us to conclude that ruby-bearing mables were formed from aluminum- rich carbonates by a regional metamorphism of deep amphibolite faces related to Bu Khang core complexe during Cenozoic tectonic activities.